Co-Administration of Anticancer Candidate MK-2206 Enhances the Efficacy of BCG Vaccine Against Mycobacterium tuberculosis in Mice and Guinea Pigs - Bouzeyen, Rania; Chugh, Saurabh; Gosain, Tannu Priya; Barbouche, Mohamed-Ridha; Haoues, Meriam; Rao, Kanury V. S.; Essafi, Makram; Singh, Ramandeep (Frontiers in Immunology, 2021)
The failure of M. bovis BCG to induce long-term protection has been endowed to its inability to escape the phagolysosome, leading to mild activation of CD8+ mediated T cell response. Induction of apoptosis in host cells plays an important role in potentiating dendritic cells-mediated priming of CD8+ T cells, a process defined as “cross-priming”. Moreover, IL-10 secretion by infected cells has been reported to hamper BCG-induced immunity against Tuberculosis (TB). Previously, we have reported that apoptosis of BCG-infected macrophages and inhibition of IL-10 secretion is FOXO3 dependent, a transcription factor negatively regulated by the pro-survival activated threonine kinase, Akt. We speculate that FOXO3-mediated induction of apoptosis and abrogation of IL-10 secretion along with M. bovis BCG immunization might enhance the protection imparted by BCG. Here, we have assessed whether co-administration of a known anti-cancer Akt inhibitor, MK-2206 enhances the protective efficacy of M. bovis BCG in mice model of infection. We observed that in vitro MK-2206 treatment resulted in FOXO3 activation, enhanced BCG-induced apoptosis of macrophages and inhibition of IL-10 secretion. Co-administration of M. bovis BCG along with MK-2206 also increased apoptosis of antigen-presenting cells in draining lymph nodes of immunized mice. Further, MK-2206 administration improved BCG-induced CD4+ and CD8+ effector T cells responses and also its ability to induce both effector and central memory T cells. Finally, we show that co-administration of MK-2206 enhanced the protection imparted by M. bovis BCG against Mtb in aerosol infected mice and guinea pigs. Taken together, we provide evidence that MK-2206-mediated activation of FOXO3 potentiates BCG-induced immunity and imparts protection against Mtb through enhanced innate immune response.